Reducing Sexual and Reproductive Health Inequities Between Natives and Migrants: A Delphi Consensus for Sustainable Cross-Cultural Healthcare Pathways - Candeias, Pedro; Alarcão, Violeta; Stefanovska-Petkovska, Miodraga; Santos, Osvaldo; Virgolino, Ana; Pintassilgo, Sónia; Pascoal, Patrícia M.; Costa, Andreia Silva; Machado, Fernando Luís (Frontiers in Public Health, 2021)
The increasing number of international migrants (ranging from 153 million in 1990 to 272 million in 2019) brought to attention the wide variation of national contexts concerning the policy measures to protect migrants' rights and ensuring their equal access to basic and essential services, namely in health. Sexual and Reproductive Health (SRH) is a key component to the overall health and quality of life and is impacted by power inequities inherent to society's institutions, environment, economics, and culture. In Portugal, guidelines for intervention in SRH are insufficient, a gap that is more pronounced with migrant populations due to the absence of culturally sensitive indicators to assess and monitor SRH. The aim of this work was 2-fold: to identify good practices in the SRH field, with a particular focus, whenever possible, on migrant populations, and to identify relevant and inclusive indicators to monitor SRH in Portugal. A Delphi panel (via online survey) with 66 experts (researchers, teachers, and health professionals) and 16 stakeholders (non-governmental organizations, civil society, and governmental organizations) was implemented in two rounds. Panelists were asked to state their level of agreement (5-point Likert-type scale) regarding four different SRH areas: Sexual Health, Reproductive Health, Social-Structural Factors, and Good Practices. Items were based on literature review and a World Café with 15 experts and stakeholders. Participation rate was 68% and response rate was 97% on the first round. From the initial list of 142 items, a total of 118 (83%) items were approved by consensus. Findings may provide extended opportunities for the healthcare system to engage in better informed decisions and more inclusive and integrative strategies regarding SRH, contributing to build political measures toward sexual and reproductive justice.